Efektivitas Penegakan Hukum Terhadap Tindak Pidana Terorisme di Indonesia: Studi Kasus Densus 88 AT Polri - Sitinjak, Rizal; Leksono, Arrum Budi; Savitri, Aisha Mutiara; Wijayanthi, Fatimah Ratna (PT Elaborium Elevasi Indonesia, 2025)
Terrorism is an international crime that jeopardizes world peace and security while severely violating human rights, particularly the right to life. In Indonesia, terrorist acts have resulted in indiscriminate loss of life, widespread fear, and extensive material damage impacting social, economic, political, and international relations. To combat terrorism, the Indonesian National Police established a specialized unit, the Special Detachment 88 Anti-Terror (Densus 88 AT), tasked with counter-terrorism efforts. This study utilizes a qualitative approach to evaluate the existing legal framework, focusing on the application of legal principles, relevant regulations, and current practices. Data collection involved analyzing primary and secondary sources, including official government documents and scholarly literature, to gain a comprehensive understanding of the legal norms relevant to the study. The results reveal that Densus 88 AT Polri, formed under Police Chief Decree No. 30/VI/2003, has been effective in counter-terrorism operations, apprehending 850 terrorists over 13 years and neutralizing key figures such as Noordin M. Top. However, concerns remain regarding alleged human rights violations, with accusations of excessive force and extrajudicial killings. Despite these criticisms, legal provisions under Law No. 5 of 2018 provide Densus 88 with the authority to use coercive measures in counter-terrorism efforts.